1997
DOI: 10.1074/jbc.272.19.12560
|View full text |Cite
|
Sign up to set email alerts
|

Mice with Genetic γ-Glutamyl Transpeptidase Deficiency Exhibit Glutathionuria, Severe Growth Failure, Reduced Life Spans, and Infertility

Abstract: A mouse mutant with glutathionuria was discovered by screening for amino acidurias in the progeny of ethylnitrosourea-mutagenized mice. Total glutathione concentration was increased in both blood and urine but decreased in liver homogenates from affected mice. Glutathionuric mice exhibited lethargy, severe growth failure, shortened life spans and infertility. ␥-Glutamyl transpeptidase activity was deficient in kidney homogenates of glutathionuric mice. The glutathionuric phenotype in these mice is inherited as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 34 publications
4
49
1
Order By: Relevance
“…3). It should be noted that these results clearly contradicted the previous reports indicating that the survival rates of the Ggt1 −/− and Ggt1 enu1/enu1 mice at 25 weeks of age are about 10 and 50%, respectively [5,14].…”
Section: Phenotypic Features Of Ggt1 Dwg/dwg Micecontrasting
confidence: 56%
See 2 more Smart Citations
“…3). It should be noted that these results clearly contradicted the previous reports indicating that the survival rates of the Ggt1 −/− and Ggt1 enu1/enu1 mice at 25 weeks of age are about 10 and 50%, respectively [5,14].…”
Section: Phenotypic Features Of Ggt1 Dwg/dwg Micecontrasting
confidence: 56%
“…Dwarfism, cataracts, infertility, and early death have been shown to be common phenotypes in these mice [5,10,14]. Glutathionemia, glutathionuria, deficiency of cellular GSH, and high susceptibility to oxidative stress have also been reported in these mice [1,5,14]. These abnormalities are reversed by administration of N-acetyl-L-cysteine (NAC), a precursor of GSH synthesis [2,11,12,14].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The g-glutamyl cycle is responsible for reabsorbing the GSH by first triggering its breakdown and then, after reabsorption of the component amino acids, catalyzing their conversion back to GSH. This idea is supported in GGT knockout mice that showed glutathionuria, Cys deficiency, and growth and reproductive defects that can be reversed by feeding acetylcysteine (Lieberman et al, 1996;Harding et al, 1997;Kumar et al, 2000).…”
mentioning
confidence: 67%
“…Earlier studies in the GGT enu1 mouse demonstrated that GGT deficiency has a dramatic impact on glutathione homeostasis. Genetic GGT deficiency in the GGT enu1 mouse impairs intracellular glutathione metabolism and results in systemic glutathionemia and oxidant stress in the kidney [22]. Previous studies with lung epithelial cells also demonstrated that when cells were exposed to quinones as an oxidantinduced stress, GGT would be increased as part of the adaptation of cells to oxidative stress by enhancing the utilization of extracellular GSH [23].…”
Section: Discussionmentioning
confidence: 99%